PENGOLAHAN KRIPIK PISANG - Jayadi Jayadi; Philipus Betaubun (Musamus University, 2019)
Merauke Regency has very abundant banana production, which in 2012 reached a production of 11,970 tons, equivalent to about 1,197,000 banana bunches per year (assuming a weight of 1 bunch = 10 kg). The types of bananas produced are more than 90% of kepok banana types, but unfortunately this huge potential has not been widely used to support local food self-sufficiency. The potential of bananas can be processed into banana chips and able to absorb and open new jobs. In the processing of banana chips, the problems encountered are the mechanical difficulties in the manual slicing process and the conventional frying process. This causes the production of banana chips not uniform, ineffective, fast rancid chips, short shelf life, decreased taste and appearance of chips. Through the application of slicing and spinner machine technology, counseling and assistance in SMEs by the Implementation Team. The IbM results obtained were uniform thickness and non-oily banana chips production, increased effectiveness of production time, supply of quality and continuous kepok bananas, orderly and good financial bookkeeping. Keyword: slicing, spiner, banana chips, not oily